2013
DOI: 10.1016/j.pedneo.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year Surveillance of Device-associated Nosocomial Infections in a Neonatal Intensive Care Unit

Abstract: Device-associated nosocomial infections was a particularly important problem in NICU. Close monitoring will decrease the rates of device-related nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 23 publications
9
35
0
2
Order By: Relevance
“…In our hospital, the detection of multi-resistant A. baumanii in ICU-acquired infections resulted in increasing the use of colistin and conseguently a significant increase in colistin resistance was detected. Increasing infection control measures by improving isolation conditions, especially in our patients with RTIs, which were frequently infected with multi-drug resistant A. baumanii, may lead to a decrease in colistin resistance rates as has been demonstrated by other studies [20,21]. In addition, we found a significant decrease in the rate of detection of all gram negative and gram positive bacteria as pathogens in BSI and UTI (Table 5, 6).…”
Section: Discussionsupporting
confidence: 73%
“…In our hospital, the detection of multi-resistant A. baumanii in ICU-acquired infections resulted in increasing the use of colistin and conseguently a significant increase in colistin resistance was detected. Increasing infection control measures by improving isolation conditions, especially in our patients with RTIs, which were frequently infected with multi-drug resistant A. baumanii, may lead to a decrease in colistin resistance rates as has been demonstrated by other studies [20,21]. In addition, we found a significant decrease in the rate of detection of all gram negative and gram positive bacteria as pathogens in BSI and UTI (Table 5, 6).…”
Section: Discussionsupporting
confidence: 73%
“…An Italian study identified 6.6% children with VAP among 451 on mechanical ventilation [25], and a mixed PICU in Australia identified 6.7% children with VAP among 269 on mechanical ventilation [26]. VAP is also common in the NICU and proportions between 6.8% and 57.0% of HAIs have been reported [34,[60][61][62][63][64][65][66]. A Spanish study identified VAP in 9.1% of 198 neonates on mechanical ventilation [67].…”
Section: Epidemiologymentioning
confidence: 99%
“…These bacteria are common in adult and paediatric intensive care units (ICUs) [3,4] and have been associated with increased mortality rates and longer length of stay [5]. Such issues frequently involve patients with acquired brain injury (ABI) [6], who present several risk factors such as mechanical ventilation, longlasting impairment of consciousness and having undergone surgery [7,8].…”
Section: Introductionmentioning
confidence: 99%